2013
DOI: 10.1155/2013/574914
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of the Artificial Neural Network Outputs in Friction Stir Lap Joining of Aluminum to Brass

Abstract: Al-Mg and CuZn34 alloys were lap joined using friction stir welding while the aluminum alloy sheet was placed on the CuZn34. In addition, the mechanical properties of each sample were characterized using shear tests. Scanning electron microscopy (SEM) and X-ray diffraction analysis were used to probe chemical compositions. An artificial neural network model was developed to simulate the correlation between the Friction Stir Lap Welding (FSLW) parameters and mechanical properties. Subsequently, a sensitivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 15 publications
(21 reference statements)
1
33
0
Order By: Relevance
“…Sensitivity was computed using the partial derivative (PaD) method. 27,28 This method starts by computing, analytically, the PaD of the prediction with respect to each input …”
Section: Assessment Of Prediction Sensitivity To Inputsmentioning
confidence: 99%
“…Sensitivity was computed using the partial derivative (PaD) method. 27,28 This method starts by computing, analytically, the PaD of the prediction with respect to each input …”
Section: Assessment Of Prediction Sensitivity To Inputsmentioning
confidence: 99%
“…In the prior literature, one can find many reports where the results of variable contribution calculated using different methods are of the significant differentiation. Shojaeefard et al [47] have published the report where there was a similarity between results obtained using the PaD method and the profile method, as well as the classical stepwise method, but the results obtained using the connection weights method were significantly different. Gevrey et al [49] employed several methods of testing the variables contribution to study a brown trout reproduction phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Combining (5) and (6): The relative contribution of each input variable on a specific output can be calculated as follows [47]:…”
Section: Partial Derivatives Methods (Pad Method)mentioning
confidence: 99%
“…In a study, checking the responsiveness of the suggested model to change in any model parameter(s) has (14). Evaluation of the suggested model quality (robustness of the model parameter) is carried out by finding out the extent of contribution of the selected functions in describing relationship between the input, the constructed (hidden), and the output variables (14).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Evaluation of the suggested model quality (robustness of the model parameter) is carried out by finding out the extent of contribution of the selected functions in describing relationship between the input, the constructed (hidden), and the output variables (14). In the present study and according to the results of sensitivity analysis (weight method / NeuralPower software), the quantitative extent of contribution of each input variables on the amount of β-CD produced, was presented in Figure 8.…”
Section: Sensitivity Analysismentioning
confidence: 99%